Verify:x3+y= (x+y)(x2+xy+y?)
Answers
To verify :
x³ + y³ = ( x + y )( x² - xy + y² )
Solution :
The term on the RHS is :
=> ( x + y )( x² - xy + y² )
=> x ( x² - xy + y² ) + y ( x² - xy + y² )
=> x³ - x²y + xy² + x²y - xy² + y³
The common terms get cancelled leaving with -
=> x³ + y³ .
Therefore LHS = RHS
Hence Verified
_____________________________
Additional Information :
(a + b)² = a² + 2ab + b²
(a + b)² = (a - b)² + 4ab
(a - b)² = a² - 2ab + b²
(a - b)² = (a + b)² - 4ab
a² + b² = (a + b)² - 2ab
a² + b² = (a - b)² + 2ab
2 (a² + b²) = (a + b)² + (a - b)²
4ab = (a + b)² - (a - b)²
ab = {(a + b)/2}² - {(a-b)/2}²
(a + b + c)² = a² + b² + c² + 2(ab + bc + ca)
(a + b)³ = a³ + 3a²b + 3ab² b³
(a + b)³ = a³ + b³ + 3ab(a + b)
(a - b)³ = a³ - 3a²b + 3ab² - b³
a³ + b³ = (a + b)( a² - ab + b² )
a³ + b³ = (a + b)³ - 3ab( a + b)
a³ - b³ = (a - b)( a² + ab + b²)
a³ - b³ = (a - b)³ + 3ab ( a - b )
__________________________________
Answer:
Correct Question :-
Verify : x³ + y³ = (x + y) (x² - xy + y²)
Solution :-
L.H.S : x³ + y³
▪️We know that,
(x + y)³ = x³ + y³ + 3xy (x + y)
So, x³ + y³ = (x + y)³ - 3xy (x + y)
(x + y)³ - 3xy (x + y)
(x + y) [ (x + y)² - 3xy ]
▪️By using the formula,
(a + b)² = a² + b² + 2ab
(x + y) [ (x² + y² + 2xy) - 3xy ]
(x + y) (x² + y² - xy)
(x + y) (x² - xy + y²)